The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmicb.2020.612135
|View full text |Cite|
|
Sign up to set email alerts
|

Active Anaerobic Archaeal Methanotrophs in Recently Emerged Cold Seeps of Northern South China Sea

Abstract: Cold seep ecosystems are developed from methane-rich fluids in organic rich continental slopes, which are the source of various dense microbial and faunal populations. Extensive studies have been conducted on microbial populations in this unique environment; most of them were based on DNA, which could not resolve the activity of extant organisms. In this study, RNA and DNA analyses were performed to evaluate the active archaeal and bacterial communities and their network correlations, particularly those partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 108 publications
1
7
0
Order By: Relevance
“…Our result of co-occurrence network showed that ANME-1b was associated strongly with SEEP-SRB2, which was consistent with the finding conducted in Haima cold seep (Zhang et al, 2020). In addition, there were proportional abundances of SEEP-SRB1, ANME-2, and Methanosarcinales in NRS.…”
Section: Variations and Relationships Of Functional Groups Depicted T...supporting
confidence: 91%
See 2 more Smart Citations
“…Our result of co-occurrence network showed that ANME-1b was associated strongly with SEEP-SRB2, which was consistent with the finding conducted in Haima cold seep (Zhang et al, 2020). In addition, there were proportional abundances of SEEP-SRB1, ANME-2, and Methanosarcinales in NRS.…”
Section: Variations and Relationships Of Functional Groups Depicted T...supporting
confidence: 91%
“…HS − + HCO − 3 + H 2 O, which is usually performed by a consortium of anaerobic methanotrophic archaea (ANME) and SRB (Hoehler et al, 1994;Cui et al, 2019). ANME, which could be classified into ANME-1, ANME-2, and ANME-3, are found widely distributed in cold seep sediments (Knittel et al, 2005;Vigneron et al, 2013;McKay et al, 2016;Niu et al, 2017;Wu et al, 2018;Cui et al, 2019;Zhang et al, 2020). ANME-1 are divided into ANME-1a and ANME-1b subgroups, whereas ANME-2 are most widely distributed and divided into ANME-2a, ANME-2b, ANME-2c, and ANME-2d subgroups (Orphan et al, 2002;Mills et al, 2003;Knittel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl coenzyme M reductase A genes in the seep sediments of the OT from the surface to bottom layers were between 10 5 and 10 8 genes g −1 (wet weight), which was higher than the abundances observed in the Haima cold seep (10 3 –10 7 genes g −1 ; Niu et al, 2017 ), northern continental slope of South China Sea (10 3 –10 5 genes g −1 ; Fan et al, 2017 ), and cold seeps of the Northern South China Sea (10 5 genes g −1 ; Zhang et al, 2020 ). In addition, we used 16S rRNA and mcrA genes to investigate the diversity of methane metabolic microbes.…”
Section: Discussionmentioning
confidence: 66%
“…Tables S1, S6 and S7), the results of the reaction-transport modeling predict the model-derived rates for Fe-AOM of up ∼0.02 μmol CH 4 cm −3 d −1 in the methanic zone (Figure 4 and Table 1). These rates are more than 20 times as big as the estimated potential Fe-AOM rates from in situ marine methanic sediments with much higher Fe 2+ concentration (180~800 µM) [20][21][22][23] (Table 1), but much lower than those derived from stimulated microbial communities in laboratory incubation studies 5,24,25,49 .…”
Section: Contribution Of Metal-aom To Methane Consumptionmentioning
confidence: 74%